2008
DOI: 10.14214/sf.258
|View full text |Cite
|
Sign up to set email alerts
|

Influence of saw and secateur pruning on stem discolouration, wound cicatrisation and diameter growth of Betula pendula

Abstract: The aim of this case study was to compare the impacts of saw and secateur pruning on silver birch (Betula pendula Roth). Data were collected from two saw pruned stands in 2005, and one secateur pruned stand in 2003. All the stands were located in southern Finland. The sample stems were felled, and their butt logs were sawn into flitches, whose knot features and colour defects were measured. In addition, discs were sawn from each stem in order to study the annual ring widths. In this material, pruning with seca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 15 publications
3
22
0
1
Order By: Relevance
“…The importance of the radial increment on branch wound occlusion was reported also for birch (Betula pendula Roth.) at the age of 33 years, where positive short-term (one year) infl uence on radial increment was found after pruning (Schatz et al, 2008). Our results, in contrast, demonstrate reduction of radial increment for Norway spruce after pruning, and the effect is signifi cant (p < 0.05) up to 3 years after this silvicultural practice, resulting in reduction of 0.28 ± 0.05 m 3 ha −1 or -7% of mean periodic volume increment.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The importance of the radial increment on branch wound occlusion was reported also for birch (Betula pendula Roth.) at the age of 33 years, where positive short-term (one year) infl uence on radial increment was found after pruning (Schatz et al, 2008). Our results, in contrast, demonstrate reduction of radial increment for Norway spruce after pruning, and the effect is signifi cant (p < 0.05) up to 3 years after this silvicultural practice, resulting in reduction of 0.28 ± 0.05 m 3 ha −1 or -7% of mean periodic volume increment.…”
Section: Discussionmentioning
confidence: 98%
“…Pruning affects diameter growth more than height growth and removal a few lowest living whorls of branches can even increase the growth of a tree (Schatz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Pruned trees had around 7% more discoloured wood within the knot than unpruned trees in this study, while there were no differences for the wood outside the knot (Table 4). Schatz et al (2008) reported that pruned branches of birch had colour defects in all directions inside the stem. The most obvious directions were tangential (47%), but the discolouration did not reach the knot-free sapwood.…”
Section: Discussionmentioning
confidence: 99%
“…A lower stocking rate will delay canopy closure, increase branch size and slow down the process of self-pruning (e.g. Cameron 1996;Schatz et al 2008), while at the same time favouring stem diameter development (Erdmann et al 1975;Niemistö 1995;Simard et al 2004;Rytter 2013). Branch traits are considered in birch breeding since branch characters such as angle, thickness and numbers are all under intermediate genetic control (Stener and Jansson 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Discolouration and decay in the centre of beech stems (hereafter referred to as red heartwood) are predominantly caused by infection and oxygen penetrating through broken and dead branches (Kučera 1991, Büren 1998, Knoke & Wenderoth 2001, Knoke 2003, Wernsdörfer et al 2006, Schatz et al 2008, Vartiamäki et al 2009, Vasaitis et al 2012. However, there is a lack of detailed information on whether bark stripping caused by logging can lead to red heartwood formation in beech.…”
Section: Introductionmentioning
confidence: 99%